Marine heatwaves and cold spells in the Northeast Atlantic: what should the UK be prepared for? - Jacobs, Zoe Louisa; Jebri, Fatma; Wakelin, Sarah; Strong, James; Popova, Ekaterina; Srokosz, Meric; Loveridge, Alexandra (Frontiers in Marine Science, 2024)
Up to now, the UK has avoided major marine heatwaves (MHWs) that cause severe damage to marine ecosystems and the blue economy. However, an unprecedented in its intensity, though short-lived, MHW occurred in UK waters in June 2023. This event sounded an alarm bell, highlighting gaps in our understanding of MHW characteristics and their potential future impacts in the UK. Here, we use a combination of remote sensing data and model output to characterise MHWs and Marine Cold Spells (MCSs) around the UK and the wider North Atlantic, and to assess the potential for concurrent biogeochemical extreme events. Results indicate that across the wider North Atlantic, the UK is not a hot spot for MHWs or MCSs but, regionally, the southern North Sea experiences the most activity. This is also the location of extreme chlorophyll-a concentrations, here termed blue waves (low chlorophyll-a) and green waves (high chlorophyll-a). However, there is not a very pronounced relationship between temperature and chlorophyll-a extremes, which may be impacted by the exact location, drivers and season of occurrence. In contrast, the southern North Sea and English Channel may experience a MHW and low near-bottom oxygen compound events year-round, which, due to the combination of thermal stress and reduced oxygen availability, may negatively impact benthic marine ecosystems. While MHWs in UK waters do not appear to be as long-lasting or intense as other well-documented events around the world now, they are projected to increase. Thus, the UK has a unique opportunity to learn from other nations and so develop robust and comprehensive policies to increase preparedness and response capability for future extreme events.